Duration of Low Temperature Exposure Affects Egg Hatching of the Colorado Potato Beetle and Emergence of Overwintering Adults - Jianghua Liao; Juan Liu; Zhijian Guan; Chao Li (Insects, 2021)
The Colorado potato beetle is a serious pest of Solanaceae in China. In early summer, cold spells in later spring may occur for brief periods in the field environmental conditions, and temperatures often deviate far below the normal temperature for short periods, such as sudden short-term low temperature, may affect the development of Colorado potato beetle eggs. This paper studies the effects of low temperature stress at 8 °C for 0 d, 1 d, 3 d, 5 d, 7 d, and 10 d on the development of Colorado potato beetle eggs. Our results show that egg survival is significantly affected by short-term low temperature exposure. The percentage of eggs hatched is significantly affected by different treatment times (p = 0.000)—the percentage of eggs hatched decreases with increased treatment time, and Colorado potato beetles will extend the wintering time of their soil to resist the effects of lower temperatures. Thus, exposure of Colorado potato beetles to a short-term low temperature affects their emergence and population growth; this study could provide information for the occurrence, monitoring, and early warning of Colorado potato beetle during short-term temperature.